The Effects of Contemporary Pop Songs on Students’ Listening Comprehension: An Experimental Study at A tutoring Center in Pare - Nabila Fauziya R; Rahmawati Sukmaningrum; Siti Musarokah (English Teaching Journal : A Journal of English Literature, Language and Education, 2026)
For English as a Foreign Language (EFL) learners in Indonesia, listening comprehension is still challenging that is often complicated by cognitive and emotional barriers such a lack of vocabulary, fast local speech rates, and low engagement with traditional teaching materials. The value of contemporary pop songs as a tactical teaching tool is the focus of this study, which investigates the potential of popular media to lessen these problems. The objective was to determine how students' listening comprehension in a non-formal education setting is affected by the presence of contemporary pop songs, with an emphasis on their capacity to identify phonetic patterns, understand popular idioms, and comprehend general context. This study highlights the novelty of employing contemporary songs with realistic speech rates and complex lyrics to maintain student interest and lower the affective filter, in contrast to other research that mostly used classical music or children's songs in formal school environments. A pre-experimental design was used in the study, which involved an intense program at a tutoring facility in Pare, Kediri. Purposive sampling was used to decide on a sample of students were highly motivated yet consistently had trouble understanding English accents. Based on to the findings, contemporary pop songs are excellent tools for instruction for casual settings. These tunes successfully reduce psychological barriers and improve long-term language retention by providing a laid-back ambiance. For the purpose to bridge the gap between textbook theory and real-world language usage in the digital age, the study suggests that educators switch from traditional audio resources to more contextual, contemporary pop songs.